Current-induced self-switching of perpendicular magnetization in CoPt single layer - Liu, Liang (2023)
All-electric switching of perpendicular magnetization is a prerequisite for the integration of fast, high-density, and low-power magnetic memories and magnetic logic devices into electric circuits. To date, the field-free spin-orbit torque (SOT) switching of perpendicular magnetization has been observed in SOT bilayer and trilayer systems through various asymmetric designs, which mainly aim to break the mirror symmetry. Here, we report that the perpendicular magnetization of CoxPt100-x single layers within a special composition range (20 < x < 56) can be deterministically switched by electrical current in the absence of external magnetic field. Specifically, the Co30Pt70 shows the largest out-of-plane effective field efficiency and best switching performance. We demonstrate that this unique property arises from the cooperation of two structural mechanisms: the low crystal symmetry property at the Co platelet/Pt interfaces and the composition gradient along the thickness direction. Compared with that in bilayers or trilayers, the field-free switching in CoxPt100-x single layer greatly simplifies the SOT structure and avoids additional asymmetric designs.